CODES ERUDITION AND SUSPENSE IN EARLY NOVELS OF DAN BROWN (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Abstract. This article examines how Dan Brown’s early fiction from 1998 to 2003 developed a stable artistic model built on coded messages, expert mediation, institutional secrecy, and accelerated pursuit. The study focuses on «Digital Fortress», «Angels & Demons», «Deception Point» and «The Da Vinci Code». It argues that Brown’s rapid rise was prepared not by one isolated bestseller, but by a repeatable compositional system in which scholarship, conspiracy and motion are fused into one reading mechanism.